2013
DOI: 10.1038/srep02094
|View full text |Cite
|
Sign up to set email alerts
|

Non-Engineered Nanoparticles of C60

Abstract: We discovered that rubbing bulk solids of C60 between fingertips generates nanoparticles including the ones smaller than 20 nm. Considering the difficulties usually associated with nanoparticle production by pulverisation, formation of nanoparticles by such a mundane method is unprecedented and noteworthy. We also found that nanoparticles of C60 could be generated from bulk solids incidentally without deliberate engineering of any sort. Our findings imply that there exist highly unusual human exposure routes t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 35 publications
1
14
0
Order By: Relevance
“…21 On the contrary, there is a little effect on either breast cancer or hepatocellular cancer cell lines with serious side effects on the liver. [17][18][19] Interestingly, while IC 50 of free drug was almost the same on normal BHK cells, as a model of normal cells, the optimized formulation has higher IC 50 (3,4, and 11 folds) compared to MCF7, HCT-116, and HepG2 cancer cell lines; respectively. This indicates that the optimized formulation has higher selectivity profile and works preferentially against cancer cells.…”
Section: In Vitro Cytotoxicity Study Of the Optimized Im-loaded Niosomesmentioning
confidence: 91%
See 1 more Smart Citation
“…21 On the contrary, there is a little effect on either breast cancer or hepatocellular cancer cell lines with serious side effects on the liver. [17][18][19] Interestingly, while IC 50 of free drug was almost the same on normal BHK cells, as a model of normal cells, the optimized formulation has higher IC 50 (3,4, and 11 folds) compared to MCF7, HCT-116, and HepG2 cancer cell lines; respectively. This indicates that the optimized formulation has higher selectivity profile and works preferentially against cancer cells.…”
Section: In Vitro Cytotoxicity Study Of the Optimized Im-loaded Niosomesmentioning
confidence: 91%
“…3 This standard definition was definitely approved and well recognized for many earlier studies in nanotechnology field. 2,4,5 From nanotechnology, NCs have been assembled from inorganic and organic materials to boost remedies efficacy, decrease their adverse events, and reinforce their therapeutic effectiveness. NCs could deliver drugs as adsorbed on or attached to their surfaces or encapsulated within their cavities.…”
Section: Introductionmentioning
confidence: 99%
“…Deguchi et al reported the preparation of fullerene nanoparticles using hand-grinding as the chemical-free processing method. [109] In addition to their solvent-free nature, these top-down approaches showed higher concentrations of the dispersed fullerene nanoparticles. X-ray diffraction patterns revealed that the crystalline structure of the fullerene remained unchanged.…”
Section: Mechanical (Chemical-free) Exfoliation Of Cnmsmentioning
confidence: 99%
“…Reproduced with permission [108]. Reproduced with permission [109]. Reproduced with permission [90].…”
mentioning
confidence: 99%
“…An alternative nC 60 formation mechanism is the physical disintegration of large particles into nanometer-sized particles 12 . Fullerite (commercially available C 60 crystals) forms particles less than 20 nm when hand-ground 13 or rubbed between the fingertips 14 . The resulting fullerite nanoparticles have the same face-centered cubic (fcc) crystal plane as the bulk fullerite powder, and form stable aqueous suspensions 14 .…”
Section: Introductionmentioning
confidence: 99%